Hubungan Karakteristik Siswa SMA Depok dan Terpaan Media dengan Sikap Kritis Menonton Televisi - Sadakita Br. Karo (Jurnal Komunikasi, 2010)
The aim of this research is to describe the relation of the characteristic and media exposure factors to the critical attitude in watching TV of the senior high school students in Depok. The sample was taken with stratified proportional random sampling, in which the first step classified the schools based on their accreditation, and then determined 35% sample of the chosen schools. Chi-Square statistic test was used to analyze the date to show the relation between the sex and the critical attitude. Correlation Pearson Product Moment was also used to show the relation between media exposure and other characteristics. The result showed that all characteristics—except sex—and also the media exposure significantly related to the critical attitude of watching behavior.